The World and God’s Word: of COVID-19, VUCA World, and Visions for the Future - Ibita, Maricel S (Archīum Ateneo, 2021)
How does one preach God’s Word in a volatile, uncertain, complex, and ambiguous (VUCA) world? As the global community is challenged by postglobal economics, postnational migration, posthuman climate crisis, post-truth politics, and the pandemic, reading the Bible needs to be reassessed. A more appropriate biblical interpretation for contemporary times has to be contextual, inclusive, integrated, and transformational. Doing so will allow us to propose alternatives to a VUCA world, one that has vision clarity, has an understanding that grasps what truly matters, has the courage to shift gears, and has the agility to act on more meaningful choices to build back better a post-COVID-19 world.